RTHP-06. IMPACT OF THE AMERICAN TAX PAYER RELIEF ACT ON STEREOTACTIC RADIOSURGERY UTILIZATION IN THE UNITED STATES. (11th November 2019) - McClelland III, Shearwood; Degnin, Catherine; Chen, Yiyi; Watson, Gordon; Jaboin, Jerry
Abstract: INTRODUCTION: For brain metastases, single-fraction stereotactic radiosurgery (SRS) spares appropriately chosen patients from the invasiveness of operative intervention and the permanent cognitive morbidity of whole brain radiation. SRS is delivered predominantly via two modalities: Gamma Knife, and linear accelerator (LINAC). The implementation of the American Tax Payer Relief Act (ATRA) in 2013 represented the first time limitations specifically targeting SRS reimbursement were introduced into federal law. The subsequent impact of the ATRA on SRS utilization in the United States (US) has yet to be examined. METHODS: The National Cancer Data Base (NCDB) from 2010–2016 identified brain metastases patients from non-small cell lung cancer (NSCLC) throughout the US having undergone SRS. Utilization between GKRS and LINAC was assessed before (2010–2012) versus after (2013–2016) ATRA implementation. Utilization was adjusted for several variables, including patient demographics and healthcare system characteristics. RESULTS: From 2012 to 2013, there was a substantial decrease of LINAC SRS in favor of GKRS overall (37% to 28%) and individually in both academic and non-academic centers. Over the three-year span immediately preceding ATRA implementation, 65.8% received GKRS and the remaining 34.2% receiving LINAC. In the four years immediately following ATRA implementation 68.0% received GKRS compared with 32% receiving LINAC; these differences were not statistically significant. CONCLUSIONS: ATRA implementation in 2013 caused an initial spike in Gamma Knife SRS utilization, followed by a steady decline, similar to rates prior to implementation. These findings are indicative that the ATRA provision mandating Medicare reduction of outpatient payment rates for Gamma Knife to be equivalent with those of LINAC SRS had a significant short-term impact on the radiosurgical treatment of metastatic brain disease throughout the US. Such findings should serve as a reminder of the importance and impact of public policy on treatment modality utilization by physicians and hospitals.